ANALISIS PENGARUH RASIO LIKUIDITAS, LEVERAGE, RASIO AKTIVITAS DAN RASIO PROFITABILITAS TERHADAP RETURN SAHAM (Studi Pada Perusahaan Jasa Sub Sektor Properti dan Real Estate yang ada di Bursa Efek Indonesia Periode Tahun 2012-2014) - Fita Dwi Hariyati; Ronny Malavia Mardani; Budi Wahono (E-JRM : Elektronik Jurnal Riset Manajemen, 2017)
AbstrakReturn is the result obtained from an investment. Stock returns are influenced byvarious factors such as the ratio of liquidity, leverage, activity and profitability. The purposeof this study was to determine the effect of the ratio of liquidity, leverage, activity andprofitability, on stock returns on service company Sub Sector Property and Real Estate.Sampling method in this research was purposive sampling and acquired 11 observationaldata as the sample. The data used in this research was secondary data. The data analysistechnique used was multiple linear regression using SPSS 20.0.Analysis method used in this research is descriptive statistics, classical assumptiontest and multiple regression analysis and t test. The results showed that the increase of stockreturns in the Company that entered the list of studies with the assumption that the variableCurrent Ratio (CR), Debt to Equity Ratio (DER), Total Asset Turnover (TATO), and Returnon Equity (ROE) did not change. For Current Ratio (CR) variable has positive andinsignificant effect on stock return, Debt to Equity Ratio (DER) variable has negative effectand not significant to stock return, Total Asset Turnover (TATO), variable has negative andinsignificant effect on stock return while Return on Equity (ROE) variable has positive andsignificant influence to stock return in service company Sub Sector Property and Real Estate.Keywords : Current Ratio (CR), Debt to Equity Ratio (DER), Total Asset Turnover (TATO),Return on Equity (ROE).